Vanadium exposure exacerbates allergic airway inflammation and remodeling through triggering reactive oxidative stress - Tu, Wei; Xiao, Xiaojun; Lu, Jiahua; Liu, Xiaoyu; Wang, Eryi; Yuan, Ruyi; Wan, Rongjun; Shen, Yingchun; Xu, Damo; Yang, Pingchang; Gong, Miao; Gao, Peisong; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Metal components of environmental PM2.5 are associated with the exacerbation of allergic diseases like asthma. In our recent hospital-based population study, exposure to vanadium is shown to pose a significant risk for current asthma, but the causal relationship and its underlying molecular mechanisms remain unclear. OBJECTIVE: We sought to determine whether vanadium co-exposure can aggravate house dust mite (HDM)-induced allergic airway inflammation and remodeling, as well as investigate its related mechanisms. METHODS: Asthma mouse model was generated by using either vanadium or HDM alone or in combination, in which the airway inflammation and remodeling was investigated. The effect of vanadium co-exposure on HDM-induced epithelial-derived cytokine release and oxidative stress (ROS) generation was also examined by in vitro analyses. The role of ROS in vanadium co-exposure-induced cytokine release and airway inflammation and remodeling was examined by using inhibitors or antioxidant. RESULTS: Compared to HDM alone, vanadium co-exposure exacerbated HDM-induced airway inflammation with increased infiltration of inflammatory cells and elevated levels of Th1/Th2/Th17 and epithelial-derived (IL-25, TSLP) cytokines in the bronchoalveolar lavage fluids (BALFs). Intriguingly, vanadium co-exposure also potentiated HDM-induced airway remodeling. Increased cytokine release was further supported by in vitro analysis in human bronchial epithelial cells (HBECs). Mechanistically, ROS, particularly mitochondrial-derived ROS, was significantly enhanced in HBECs after vanadium co-exposure as compared to HDM challenge alone. Inhibition of ROS with its inhibitor N-acetyl-L-cysteine (NAC) and mitochondrial-targeted antioxidant MitoTEMPO blocked the increased epithelial release caused by vanadium co-exposure. Furthermore, vitamin D3 as an antioxidant was found to inhibit vanadium co-exposure-induced increased airway epithelial cytokine release and airway remodeling. CONCLUSIONS: Our findings suggest that vanadium co-exposure exacerbates epithelial ROS generation that contribute to increased allergic airway inflammation and remodeling.